Gadd45g is required for timely Sry expression independently of RSPO1 activity. Issue 6 (22nd April 2022) - Warr, Nick; Siggers, Pam; May, Joel; Chalon, Nicolas; Pope, Madeleine; Wells, Sara; Chaboissier, Marie-Christine; Greenfield, Andy
Abstract : Sex determination in mammals is controlled by the dominance of either pro-testis (SRY-SOX9-FGF9) or pro-ovary (RSPO1-WNT4-FOXL2) genetic pathways during early gonad development in XY and XX embryos, respectively. We have previously shown that early, robust expression of mouse Sry is dependent on the nuclear protein GADD45g. In the absence of GADD45g, XY gonadal sex reversal occurs, associated with a major reduction of Sry levels at 11.5 dpc. Here, we probe the relationship between Gadd45g and Sry further, using gain- and loss-of-function genetics. First, we show that transgenic Gadd45g overexpression can elevate Sry expression levels at 11.5 dpc in the B6.Y POS model of sex reversal, resulting in phenotypic rescue. We then show that the zygosity of pro-ovarian Rspo1 is critical for the degree of gonadal sex reversal observed in both B6.Y POS and Gadd45g -deficient XY gonads, in contrast to that of Foxl2 . Phenotypic rescue of sex reversal is observed in XY gonads lacking both Gadd45g and Rspo1, but this is not associated with rescue of Sry expression levels at 11.5 dpc. Instead, Sox9 levels are rescued by around 12.5 dpc. We conclude that Gadd45g is absolutely required for timely expression of Sry in XY gonads, independently of RSPO1-mediated WNT signalling, and discuss these data in light of our understanding of antagonistic interactions between the pro-testis and pro-ovary pathways.